Examining Community Financing of School Human Resources and its Effects on Quality Education in Kisumu County, Kenya - James Ochieng Sika; Duncan Owiye; Hezekiah Adwar Othoo (Indonesian Educational Research Journal, 2024)
Education is an essential tool for human life that helps pupils to optimize their potential This Study was based Kisumu County was chosen for its below average KCSE mean score of 4.08 (D+) in 2017 compared to the average mean of 6 (C); low teacher student ratio at 1:59 compared to the required 1:45 and absolute poverty index of 41% compared to the national poverty index of 35.6. The purpose of this study was to analyze community financing of human resources in public secondary schools and its effect on quality of education in Kisumu County, Kenya. A descriptive and correlation research design was used in the study. Stratified simple random sampling procedure was used to sample the 64 public secondary schools in Kisumu County from which 64 school principals, 64 BOM Chairpersons, 16 CBOs and 387 purposively selected students were used for the study. Reliability of the instruments was calculated by using the test re- test and was calculated at Pearson r coefficient of 0.879. The study showed that there was strong positive correlation of 0.865 between community financing of human resources and academic performance. The study concluded that community financing of human Resources significantly influences the academic performance of learners to a great extent. The study recommended Free Day Secondary Education funding should be increased in order to achieve fully the objectives of the secondary education policy.